Type 1 Diabetes Mellitus Presenting as Distal Renal Tubular Acidosis (RTA Type 1) - Garg, Mohit; Kant, Ravi (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: Type 1 Diabetes Mellitus (DM) is an autoimmune process which causes destruction of b-cells and absolute insulin deficiency. This insulin deficiency prone patient to hyperglycemia and resultant early micro-vascular and macro-vascular complications. Macro-vascular complication seen early in diabetes are CAD, CVA and PAD. In micro-vascular complications, we have retinopathy, neuropathy and nephropathy. In diabetic nephropathy, usually glomerular injury is widely described in literature but little is known about the tubular changes. We report a case which has tubular damage in the form of distal tubular damage causing renal tubular acidosis. Patient has classical bilateral nephrocalcinosis, normal anion gap acidosis and persistently low HCO3. This entity in type 1 DM is not reported in literature. Case: Patient S, 42 yr Male with Type 1 DM for 15 years on Inj. Insulin mixtard presented to emergency with swelling of bilateral lower limb associated with pain/tingling and numbness for 3 months. Conclusion: In a patient with type 1 DM, acidosis can occur due to causes other than DKA and workup should be done if acidosis persists even after treatment.